Implementation strategies proposed by the teams. - Maria A. Afadapa (22683548) (2025)
We organized an Innovation Bootcamp for young people in Nigeria to develop strategies promoting the uptake of the hepatitis B birth dose vaccine among newborns, which remains low, with an estimated coverage of 52%. This event was a collaborative, cross-disciplinary capacity-building platform to generate creative solutions addressing barriers to Hepatitis B vaccine uptake. The purpose of this study was to describe the bootcamp activities that address this gap and evaluate the impact of an Innovation Bootcamp designed to build research capacity among young Nigerians. The bootcamp was informed by Participatory Action Research focused at engaging young people as co-researchers to investigate and address issues affecting their respective communities using the PEN-3 cultural model. Qualitative data from the community needs assessment were analyzed using a thematic analysis framework to identify and synthesize emerging themes. Socio-demographic characteristics of the participants were collected, and a pre- and post-survey was administered. The participants’ knowledge of hepatitis B and research skills were compared using the Wilcoxon test. Our results included five teams composed of fifteen participants with a mean age of 25.5 years, originating from the Southern regions of Nigeria. The post-survey showed significant improvements in participants’ knowledge and research skills, with knowledge increasing by 21.6% (mean score: 39.7 to 48.3, p = 0.010) and research skills by 36.4% (mean score: 56.1 to 76.5, p < 0.001). Each team co-designed implementation strategies, including referral pathways from traditional birth attendants to formal health centers, comprehensive training workshops, and trusted community leaders as vaccination ambassadors. In conclusion, the bootcamp demonstrated its effectiveness in strengthening capacity and increasing knowledge (although in a small sample size), which contributed to informing the development of implementation strategies. Findings from the pilot studies will ultimately inform future research focused on promoting and sustaining youth-derived vaccination service delivery strategies in Nigeria.